Attitudes of Health Care Professionals Toward Older Adults' Abilities to Use Digital Technology: Questionnaire Study - Mannheim, Ittay; Wouters, Eveline J M; van Boekel, Leonieke C; van Zaalen, Yvonne (JMIR Publications, 2021)
BackgroundDigital technologies (DTs) for older adults focus mainly on health care and are considered to have the potential to improve the well-being of older adults. However, adoption rates of these DTs are considered low. Although previous research has investigated possible reasons for adoption and acceptance of DT, age-based stereotypes (eg, those held by health care professionals) toward the abilities of older adults to use DTs have yet to be considered as possible barriers to adoption. ObjectiveThe aim of this study was to investigate the influencing role of ageism in the context of health care professionals attitudes toward older adults' abilities to use health care DT. A further goal was to examine if social comparison and stereotype activation affect and moderate this association. MethodsA new measurement to assess health care professionals' attitudes toward older adults using technology (ATOAUT-10) was developed and used in 2 studies. Study 1 involved the development of the ATOAUT-10 scale using a principal component analysis and further examined health care professionals' attitudes toward the use of health care DTs and correlations with ageism. Study 2 further explored the correlation between ageism and ATOAUT in an experimental design with health care professionals. ResultsIn study 1, physiotherapists (N=97) rated older adults as young as 50 years as less able to use health care DT compared to younger adults (P<.001). A multiple regression analysis revealed that higher levels of ageism, beyond other predictors, were predictive of more negative ATOAUT, (β=.36; t=3.73; P<.001). In study 2, the salience of age was manipulated. Health care professionals (N=93) were randomly assigned to rate the abilities of a young or old person to use health care DT. Old age salience moderated the correlation between ageism and ATOAUT (R2=0.19; F6,85=3.35; P=.005), such that higher levels of ageism correlated with more negative ATOAUT in the old age salient condition, but not the young condition. Stereotype activation accounted for health care professionals' attitudes more than did the experience of working with older patients or the professionals' age. ConclusionsNegative and ageist attitudes of health care professionals can potentially affect how older adults are viewed in relation to DT and consequently might influence actual use and adoption of technology-based treatment. Future studies should broaden the validation of the ATOAUT-10 scale on more diverse samples and focus on the discriminatory aspect of ageism and self-ageism of older adults. This study calls for a focus on ageism as a determinant of adoption of DT.